Public debt dynamics and real exchange rate volatility: Evidence from South Africa - Tyani, Yonela; Mbaleki, Chuma; Nodo, Asive (Economic Journal of Emerging Markets, 2026)
Purpose — This paper examines the relationship between South Africa’s rising public debt and real exchange rate (RER) volatility. Over the past two decades, the country has experienced an alarming increase in external and domestic debt levels, accompanied by episodes of exchange rate instability and deteriorating economic performance. Method — Using annual data from 2000 to 2024, we estimate an ARDL model to assess the nexus between debt and exchange rate volatility. Findings — The results suggest that public debt is a significant driver of exchange rate volatility and rand depreciation. However, interest rates, inflation, and trade openness are key factors responsible for significant fluctuations in the exchange rate in South Africa. Similar results are obtained in both the short-run and long-run estimation.Implications — The paper recommends firm government controls designed to prevent sharp capital movements (inflows or outflows) that could destabilise the rand. This can be achieved by maintaining a favourable trade balance, targeting inflation, and adjusting monetary policy. Secondly, the government can diversify the composition of its debt currency. This helps reduce volatility in debt-servicing payments and further stabilises government budgets and fiscal planning.Originality — There is little empirical literature on the direct relationship between public debt and real exchange rate volatility in South Africa. This study aims to fill the gap by providing a novel empirical assessment of the long- and short-run dynamics between rising public debt and real exchange rate volatility.